The ACTN3 XX genotype's underrepresentation in Japanese elite wrestlers - Kikuchi, N.; Ueda, D.; Min, S.-k.; Nakazato, K.; Igawa, S. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To examine the relationship between ACTN3 polymorphisms and level of athletic performance in Japanese wrestlers. Methods: The control group consisted of 243 healthy Japanese individuals. The authors divided 135 wrestlers into 3 groups based on their results in national or international competitions. They classified as elite 24 wrestlers who had placed in the top 8 in a world championship or participated in Olympic games, 28 wrestlers who had participated in world championships or become champions in Japan`s national championships were classified as subelite, and 83 wrestlers were classified as national (N-W, ie, national-level wrestler). In addition, the authors combined the elite and subelite to form the classification international-level wrestlers (I-W). Results: The frequency of the null X allele and the XX genotype were significantly lower in the I-W group than in the control group. However, there was no significant difference in ACTN3 genotype or allele frequency between the N-W and control groups. The frequency of the ACTN3 XX genotype in the elite groups was lower than that of all groups, and a linear tendency was observed between ACTN3 XX genotype and athletic status. Conclusions: In conclusion, the data indicated that ACTN3 polymorphisms were related to athletic performance in Japanese wrestlers.